Window displays and the Filipino consumer - Masadao, Josefina Reyes; Mayo, Adelaida Villaraza (1989.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Show windows -- Philippines